Cutaneous phaeohyphomycosis caused by Alternaria longipes in an immunosuppressed patient. - Gené, J (1995)
Alternaria longipes was reported as the agent of a cutaneous infection in a patient with a neoplastic disease. The fungus has not been reported previously as causing disease in humans. It was distinguished by its rather small conidia with smooth or slightly verruculose walls and a pale brown beak which rarely extended into a secondary conidiophore. In vitro inhibitory activities of amphotericin B, ketoconazole, itraconazole, and miconazole were shown.